2023
DOI: 10.1111/pbi.14054
|View full text |Cite
|
Sign up to set email alerts
|

A systematic dissection in oilseed rape provides insights into the genetic architecture and molecular mechanism of yield heterosis

Abstract: Summary Heterosis refers to the better performance of cross progeny compared with inbred parents, and its utilization contributes greatly to agricultural production. Several hypotheses have been proposed to explain heterosis mainly including dominance, over‐dominance (or pseudo‐overdominance) and epistasis. However, systematic dissection and verification of these hypotheses are rarely documented. Here, comparison of heterosis level across different traits showed that the strong heterosis of composite traits (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“… 11 In maize, through a design of multiple linked F 1 populations containing 42,840 F 1 hybrids and genome-wide association study, an instance of epistasis was revealed where one recessive, deleterious maternal allele, Brachytic2 , repressed the favorable Ubiquitin3 locus in the maternal lines, while the paternal allele alleviated this repression and thus recovered plant height and ear weight in hybrids. 10 The genomic architectures of heterosis in rice, maize, wheat, and other crops were also characterized using the population-based method, 6 , 7 , 12 , 13 , 26 , 27 , 44 which uncovered many novel loci functioning in heterosis via dominance, overdominance, and epistasis. These loci were dynamically predominant for different heterotic traits during plant life cycle and could serve as important references for genotype-based parent selection in hybrid breeding ( Figure 1 B).…”
Section: Introductionmentioning
confidence: 99%
“… 11 In maize, through a design of multiple linked F 1 populations containing 42,840 F 1 hybrids and genome-wide association study, an instance of epistasis was revealed where one recessive, deleterious maternal allele, Brachytic2 , repressed the favorable Ubiquitin3 locus in the maternal lines, while the paternal allele alleviated this repression and thus recovered plant height and ear weight in hybrids. 10 The genomic architectures of heterosis in rice, maize, wheat, and other crops were also characterized using the population-based method, 6 , 7 , 12 , 13 , 26 , 27 , 44 which uncovered many novel loci functioning in heterosis via dominance, overdominance, and epistasis. These loci were dynamically predominant for different heterotic traits during plant life cycle and could serve as important references for genotype-based parent selection in hybrid breeding ( Figure 1 B).…”
Section: Introductionmentioning
confidence: 99%